Content analysis of combined anti-tuberculosis drugs - Nevzghoda, Oleksandr; Osyntseva, Alina; Shapovalov, Valentyn; Titarenko, Iurii; Dovzhuk , Viktoria; Shapovalova, Viktoriia; Shapovalov, Valerii (Annals of Mechnikov’s Institute, 2025)
Introduction. The fight against tuberculosis remains one of the main challenges in global public health. The emergence of multidrug-resistant tuberculosis (MDR-TB) has significantly complicated the effectiveness of standard anti-TB therapy. The use of combined fixed-dose drug formulations is a key approach to increase treatment adherence and therapeutic efficacy. Materials and methods. The study involved a content analysis of the assortment of combined anti-tuberculosis medicines registered in Ukraine. The data were grouped by manufacturers using Sturges’ formula to create discrete variation series and a frequency polygon. The availability of drugs in the State Formulary and the national legislation was also analyzed as of the current edition approved by Order of the Ministry of Health of Ukraine dated March 12, 2024, No. 418. Results and discussion. The study found that the use of combined anti-tuberculosis drugs is critical for the treatment of MDR-TB. The analysis showed that fixed-dose combinations offer pharmacological benefits, improve patient compliance, and reduce the risk of developing resistance. The Ukrainian pharmaceutical market offers a limited number of such combinations, with a significant share represented by foreign manufacturers. The current State Formulary reflects the need to expand access to essential anti-tuberculosis drug combinations. Conclusions. The combined use of anti-tuberculosis drugs is an effective strategy in MDR-TB treatment. Ensuring availability and expanding the range of fixed-dose combinations in Ukraine is vital for improving treatment outcomes and aligning with WHO recommendations.